Evidence for Host Epigenetic Signatures Arising From Arbovirus Infections: A Systematic Review - Aguiar, Gabriella Pequeno Costa Gomes de; Leite, Claudio Manuel Gonçalves da Silva; Dias, Beatriz; Vasconcelos, Silvania Maria Mendes; Moraes, Renata Amaral de; Moraes, Maria Elisabete Amaral de; Vallinoto, Antonio Carlos Rosario; Macedo, Danielle Silveira; Cavalcanti, Luciano Pamplona de Goes; Miyajima, Fabio (Frontiers in Immunology, 2019)
Background: Arbovirus infections have steadily become a major pandemic threat. This study aimed at investigating the existence of host epigenetic markers arising from the principal arboviruses infections impacting on human health. We set to systematically review all published evidence describing any epigenetic modifications associated with infections from arboviruses, including, but not limited to, microRNAs, DNA methylation, and histone modifications. Methods: A comprehensive search was conducted using the electronic databases PubMed, Science Direct and Cochrane Library from inception to January 4th, 2018. We included reports describing original in vivo or in vitro studies investigating epigenetic changes related to arbovirus infections in either clinical subjects or human cell lines. Studies investigating epigenetic modifications related to the virus or the arthropod vector were excluded. A narrative synthesis of the findings was conducted, contextualizing comparative evidence from in vitro and in vivo studies. Results: A total of 853 unique references were identified and screened by two independent researchers. Thirty-two studies met the inclusion criteria and were reviewed. The evidence was centered mainly on microRNA and DNA methylation signatures implicated with secondary Dengue fever. Evidence for recent epidemic threats, such as the infections by Zika or Chikungunya viruses is still scant. Conclusions: Major epigenetic alterations found on arboviruses infections were miR-146, miR-30e and the Dicer complex. However, existing studies frequently tested distinct hypotheses resulting in a heterogeneity of methodological approaches. Whilst epigenetic signatures associated with arbovirus infections have been reported, existing studies have largely focused on a small number of diseases, particularly dengue. Validation of epigenetic signatures have an untapped potential, but concerted investigations are certainly required to deliver robust candidates of clinical utility for diagnosis, staging and prognosis of specific arbovirus diseases.